Metal‐Based Catalytic Drug Development for Next‐Generation Cancer Therapy. (29th June 2021) - Fan, Zhongxian; Huang, Juyang; Huang, Huaiyi; Banerjee, Samya
Abstract: Considering the high increase in mortality caused by cancer in recent years, cancer drugs with novel mechanisms of anticancer action are urgently needed to overcome the drawbacks of platinum‐based chemotherapeutics. Recently, in the area of metal‐based cancer drug development research, the concept of catalytic cancer drugs has been introduced with organometallic Ru II, Os II, Rh III and Ir III complexes. These complexes are reported as catalysts for many important biological transformations in cancer cells such as nicotinamide adenine dinucleotide (NAD(P)H) oxidation to NAD +, reduction of NAD + to NADH, and reduction of pyruvate to lactate. These unnatural intracellular transformations with catalytic and nontoxic doses of metal complexes are known to severely perturb several important biochemical pathways and could be the antecedent of next‐generation catalytic cancer drug development. In this concept, we delineate the prospects of such recently reported organometallic Ru II, Os II, Rh III and Ir III complexes as future catalytic cancer drugs. This new approach has the potential to deliver new cancer drug candidates. Abstract : Metal‐complex‐mediated in‐cell catalysis, which can create intracellular redox imbalance or metabolic disruption, is emerging as a new methodology for next‐generation catalytic cancer drug development. In this context, organometallic Ru II, Os II, Rh III and Ir III complexes are highly important. Herein we critically discuss the future of such complexes as catalytic cancer drug candidates.